THE MOST CRINGE – WORTHY FACT ABOUT DOUBLE BURDEN OF MALNUTRITION; SOCIAL DETERMINANTS - Ahmad Ansari, Pro. Murtuja (International Journal of Multidisciplinary Research and Studies, 2021)
We investigate the social determinants moreover because of the geographical variations of under- and over-nutrition in Indonesia using the biggest public health study ever conducted within the country, the National Basic Health Research 2007 (N¼ 645,032). Multilevel multinomial logistic regression and quintile regression models are ﬁtted to estimate the association between nutritional status and several socio-economic indicators at both the individual and district levels. We ﬁnd that: (1) education and income reduce the chances of being underweight by 10–30% but at the identical time increase those of overweight by 10–40%; (2) independent from the compositional effect of poverty, income inequality is detrimental to population health: a 0.1 increase within the Gini coefficient is related to an 8–12% increase within the odds of a personality’s being both under- and overweight; and (3) the consequences that these determinants have upon nutritional status aren’t necessarily homogeneous along the continuum of body mass index. Equally important, our analysis reveals that there’s substantial spatial clustering of areas with an elevated risk of under-or over-nutrition across the 17,000-island archipelago. The income inequality accompanying Indonesia’s economic process may aggravate the twin burden of under and over nutrition.